Tripartite Anthropology In Patristic Writings: A Modern Reflection - Janjic, Sinisa (Université d'Ottawa | University of Ottawa, 2026)
This study explores the tripartite anthropology of the Church Fathers - body, soul, and spirit - as a central framework for understanding the human person in early Christian thought. Focusing on key texts by Justin Martyr, Tatian, Irenaeus, Origen, and Augustine, it asks whether there is a discernible system behind their works and does their thinking provide us with a working model of a tripartite person? Within this tripartite construct, the role of spirit is closely examined. This thesis systematizes the thoughts of the selected Church Fathers, in order to build a provisional theological model of a human being, thus providing a basis or a rationale for the foundation of the model.
Keywords: tripartite anthropology, Tripartite Theology, spirit, human spirit, Church Fathers, systematic theology, Justin Martyr, Tatian, Irenaeus, Origen, Augustine